Leaders’ supervisory roles in service-learning programmes and implications for university graduates in Nigeria: a systematic review - Eniola-Arigbe , Yetunde; Awodiji, Omotayo Adewale (Journal of Management and Business Education, 2025)
There is a gap between graduates' academic knowledge and the skills demanded in the labour market. This skill mismatch has driven scholars in the field of education to explore the potential of service learning in equipping graduates with relevant skills to meet evolving demands in the world of work. However, there exists a need for more research concerning the roles of supervisors in service-learning programmes and the potential for service-learning among graduates within the Nigerian university setting. This study systematically reviews the leadership supervisory roles in service-learning programmes and their implications for graduates' employability. Following PRISMA methodology, the systematic literature review examines 14 articles published between 2012 and 2023 in four established databases—Web of Science, Scopus, Eric, and DOAJ. This review reveals a scarcity of scholarly exploration into the roles of supervisors in service-learning programmes within the Nigerian university education system. The outcomes of this study provide a foundation for informed decision-making in educational policy and practice, guiding policymakers to allocate resources effectively and administer targeted training programmes to address the challenges associated with service learning in university education. University education curricula should incorporate service-learning programmes to enhance graduate employability, career advancement, and economic growth.